Socioeconomic Inequalities in the Prevalence of Diabetes in Argentina: A Repeated Cross-Sectional Study in Urban Women and Men - Rojas-Roque , Carlos (2022)
“This study measured the socioeconomic inequalities in the prevalence of diabetes between 2005 and 2018 in an urban Argentinian population. Data were obtained from the repeated crosssectional surveys “National Survey of Risk Factors” (ENFR is its acronym in Spanish). From 2005 to 2018, four rounds of ENFR were administered to men and women over 18 years of age. Concentration curves (CC) and the Erreygers concentration index (ECI) were used to describe the socioeconomic inequalities in diabetes’ prevalence. A decomposition analysis was performed to determine the contribution of each variable to inequality in diabetes’ prevalence. Data from 41,219 (2005), 34,583 (2009), 32,232 (2013), and 29,094 (2018) individuals were analyzed. Women reported a greater prevalence of diabetes compared with men for all the years included. According to the CC and ECI, we found no evidence of inequality in men throughout all study years. For women, throughout all years, the CCs were above the line of equity, and the ECIs during all the years were negative and different from zero (p < 0.01). For women, we found no evidence of a reduction in inequalities between 2005 and 2018 (p = 0.475). The socioeconomic inequality for women was largely driven by public insurance, primary and secondary education, and employment. Diabetes’ prevalence was not associated with socioeconomic status in men, while the prevalence of diabetes in women was more concentrated among poorer women. During the 13 years, there was no evidence of a reduction of inequality in women, noting that interventions must prioritize and should focus on the main contribution of inequalities, such as education and employment.“